2022
DOI: 10.3390/su14127420
|View full text |Cite
|
Sign up to set email alerts
|

Pricing Problems in the Pharmaceutical Supply Chain with Mixed Channel: A Power Perspective

Abstract: This paper builds Pharmaceutical Manufacturer Stackelberg, Pharmacy Stackelberg and Nash game models with and without price cap regulation. The optimal pricing, performance and social welfare are derived and compared in three different power structures to find out how price cap regulation and power structures affect the drug supply chain. More power over other supply chain members always allows the pharmaceutical manufacturer to obtain more profits. However, the pharmacy cannot always benefit from its dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…The detailed mechanism offers further theoretical contributions in the studies of regulation on pharmaceutical prices. According to a previous study of regulation on pharmaceutical prices, few studies revealed the factors leading to unreasonable pharmaceutical prices from the perspective of medical service provision [ 7 , 10 , 16 , 35 ]. This study explores this detailed impact mechanism, which offers several contributions to the regulation of pharmaceutical prices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed mechanism offers further theoretical contributions in the studies of regulation on pharmaceutical prices. According to a previous study of regulation on pharmaceutical prices, few studies revealed the factors leading to unreasonable pharmaceutical prices from the perspective of medical service provision [ 7 , 10 , 16 , 35 ]. This study explores this detailed impact mechanism, which offers several contributions to the regulation of pharmaceutical prices.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, regulation is designed to overcome market failures and thereby redirect the market to a state of Pareto equilibrium. When it comes to the pharmaceutical market, according to prior studies, this market is a main object of regulation [ 7 , 10 ]. The first reason for this is that the market for medical services has strict positive externalities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, to ensure sustainable supply and reduce prices [4,5], China has widely implemented centralized procurement at the provincial level since 2009 [6]. Nevertheless, this policy subsequently raised concerns about the quality of Chinese generic drugs and the problem of shortages of procured drugs with low levels of cost or consumption [7,8], which led to the introduction of policies on generic drug consistency evaluation and volume-based centralized procurement [9,10]. In order to tackle the problem of high drug prices, China has gradually abolished markup charging of drugs in public hospitals since 2009, compensating hospitals' income loss from drug sales through government subsidies.…”
Section: Introductionmentioning
confidence: 99%